Zbornik povzetkov študentskih projektov / 6. letna konferenca mehtronike 2017, Maribor - Marina Bajić; Hace, Aleš; Župerl, Uroš (2017)
Book of Abstracts, Student Projects / 6th Conference on Mechatronics, Maribor. The Faculty of Electrical Engineering, Computer Science and Informatics (FERI) and the Faculty of Mechanical Engineering (FS) of the University of Maribor (UM) are the only ones in Slovenia to conduct quality independent study programs of Mechatronics at undergraduate university and higher professional level 1 and at postgraduate master's level 2 studies. The engineer of Mechatronics is in the domestic industry, and even more so in our neighborhood, an extraordinary and increasingly sought-after profile, and experts in this field are involved in the production and development of the most modern mechatronics products with high added value. The study programs of Mechatronics at the University of Maribor are distinguished by their project oriented education, where students work in groups on various practical mechatronic problems of full modern technological challenges. The results of their project work are presented by students at the end of the school year at the Mechatronics Summer Conference. Thus, this year, our students at the conference organized on June 29, 2017 present a total of 31 projects, of which 7 projects are students of a higher education program, 17 projects are students of a university undergraduate study program, and 7 projects are students of the postgraduate master's study program. Projects refer to industrial mechatronics, product mechatronics, production and service robotics, automation, power electronics system, etc. The summaries of these projects are gathered in the present encyclopedia, where basic information can be found, and you will be able to learn more details at the conference. All projects are interesting and therefore we invite you on behalf of the FERI and FS organizers to take part in this year's Mechatronics Summer Conference!
Keywords: mechatronics; robotics; automatics; industry; student projects